PENGARUH PEMAHAMAN PERATURAN, OMSET, KUALITAS PELAYANAN, DAN SANKSI TERHADAP KEPATUHAN WAJIB PAJAK (Studi Kasus Pada Wajib Pajak Restoran di Kota Pekanbaru) - Rizajayanti, Diyan Sulastika; Basri, Yessi Mutia; ', Supriono (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The purpose of this study was to determine whether there is a significant effect of understanding the rules, turnover, quality of service, and sanctions against tax compliance Taxpayers Restaurants in Pekanbaru. The sampling technique in this research is accidental sampling that taxpayer Pekanbaru restaurants in town that are willing to meet and fill out the questionnaire directly. In this case the population is obtained by researchers amounted to 1,463 population and the sample was 94 respondents. The technique of collecting data using questionnaires and testing the hypothesis by using multiple regression analysis. In this study, the calculation of dependent and independent variables using indicators from previous research questionnaire. The independent variable understanding of regulations, partially have a significant impact on tax compliance restaurant, but the variable turnover, quality of service and the sanctions do not have a significant effect partially against tax compliance restaurant. The results from coefficient determination (adjusted R2) test is worth 0.383. The conclusion from overall effect of independent variables is 38.3% while the remaining 61.7% is influenced by other independent variables that were not examined and used in this study.Keyword : Understanding The Rules, Turnover, Quality Of Service, Sanctions, and Compliance Taxpayers.